The counter-archive in art: The shamanic power of a reverse antropology (Palíndromo, 2017)
A present time adorned by surrea-listic traits gradually brings us closer to a seemingly distant reality, described in the apocalyptic prophecies of diverse beliefs. The overcoming of barbarism is on the edge of an unreachable path. The resumption of terror is due to the state of crisis - usually simulated - in calling for a radical change by various actors, not in-frequently invoking unprecedented acts of violence against a divergent thinking, plowing ground where an amnesia on the characteristics of barbarism, conve-niently cultivated, blooms. The fall of the sky, announced by Yanomami mytholo-gy, would be the summit of this journey destined to the multiple decline of the ci-vilizatory bases, with their vices of origin that fail them to the failure and that, con-sequently, they cause the indiscriminate collapse to the conniving and divergent ones to the process. The text aim to pre-sent the works of artists that align with the discordance, producing works, ma-nifestos and denunciations of the abuses contained in the exercise of power, in de-mocracy or in the exception state.
Keywords: political art; archive; memory and violency